Application of Acupressure Therapy to Increase Breast Milk Production in Spontaneous Post Partum Mothers - Iif Taufiq El Haque; Elis Roslianti; Ade Fitriani; Indah Dwi Lestari (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Introduction: Acupressure is a non-pharmacological technique that can increase breast milk production, which is useful for increasing body stamina, improving blood circulation, reducing pain, reducing stress, or calming the mind. Acupressure serves to increase the hormone oxytocin, which can calm the mother, so that breast milk comes out by itself. Objective: This case study is to determine the effectiveness of acupressure therapy in increasing breast milk production in spontaneous postpartum clients. Method: This study uses a case study design with a nursing care approach that focuses on nursing interventions. The research was conducted in Teratai Room 2, RSUD Banjar City, from June 2, 2023, to June 4, 2023. The participants in this study were Mrs. W, 32 years old, a woman who complained that her milk production was low. The nursing process is focused on the main problem, namely ineffective breastfeeding. Objective data and subjective data are used as references on a regular basis to obtain results when an assessment is carried out. The instruments used were leaflets, observation sheets, and all the tools used in physical examinations. The focus of the intervention was the application of acupressure therapy to increase breast milk production in spontaneous postpartum mothers. Result: This case study is supported by objective and subjective data. The objective data obtained were that the patient admitted that the breasts did not feel tight, the breasts were clean, there were no lesions or redness, blood pressure 120/80 mmHg, temperature 36.6oC, pulse 86 x/min, respiration 20 x/min. subjective data, namely the recognition of patients complaining of very little milk expenditure. Conclusion: The intervention is thought to be effective against the effect of acupressure therapy on increasing milk production in postpartum patients. Theoretically, this research does not conflict with previous research, so it can be used as a reference in future research. Meanwhile, clinically, interventions made for ineffective breastfeeding problems can be an alternative to eliminating nursing problems in hospitals, health centers, or other health clinics.